2019
DOI: 10.1177/2050640619868352
|View full text |Cite
|
Sign up to set email alerts
|

Individualized risk prediction of significant fibrosis in non‐alcoholic fatty liver disease using a novel nomogram

Abstract: Background Fibrosis is deemed to be a pivotal determinant of the long-term prognosis in non-alcoholic fatty liver disease (NAFLD). Objective We aimed to develop a novel nomogram-based non-invasive model to accurately predict significant fibrosis in patients with NAFLD. Methods We designed a prospective cohort study including 207 patients with biopsy-proven NAFLD. Detailed anthropometric and fibrosis-related laboratory parameters were collected. A nomogram was established based on variables that were independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 29 publications
0
37
0
Order By: Relevance
“…However, another meta-analysis indicated that APRI and FIB-4 had only moderate sensitivity and accuracy for diagnosis of liver fibrosis in chronic hepatitis B patients, which suggested they were not ideal substitutes for liver biopsy [ 39 ]. Regarding NAFLD, recent studies showed that APRI could better distinguish fibrosis stage F2-3 from F0-1 than FIB-4 [ 40 , 41 ]. The GPR developed by Lemoine et al was shown to be more accurate than the APRI and FIB-4 [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, another meta-analysis indicated that APRI and FIB-4 had only moderate sensitivity and accuracy for diagnosis of liver fibrosis in chronic hepatitis B patients, which suggested they were not ideal substitutes for liver biopsy [ 39 ]. Regarding NAFLD, recent studies showed that APRI could better distinguish fibrosis stage F2-3 from F0-1 than FIB-4 [ 40 , 41 ]. The GPR developed by Lemoine et al was shown to be more accurate than the APRI and FIB-4 [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the diagnostic performance of these non-invasive tests is satisfactory for ruling out advanced fibrosis, their performance is not adequate for diagnosing clinically significant liver fibrosis. 5,6 A recent meta-analysis showed that even low levels of liver fibrosis are associated with overall and liver-specific mortality, and these data are supported by the results of a large biopsy study with a mean of 20 years follow-up showing that advanced fibrosis was associated with liver-specific morbidity and overall mortality. 3 Additionally, distinguishing between NAFLD with or without significant fibrosis is clinically important for determining the clinical prognosis of these patients.…”
Section: Introductionmentioning
confidence: 89%
“…This is an observational study of the well-characterized Prospective Epidemic Research Specifically Of NASH (PERSONS) cohort 12. Patients enrolled in this study fulfilled the following criteria: (1) age between 18–75 years; (2) presence of hepatic steatosis on liver ultrasound or other imaging techniques, and then confirmed by liver biopsy, in the absence of other competing causes of chronic liver diseases (as specified in the Results section); and (3) provided informed written consent prior to their inclusion in the study.…”
Section: Methodsmentioning
confidence: 99%